2007
DOI: 10.4028/www.scientific.net/amr.26-28.1121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclic Strain Rate on Environmental Fatigue Behaviors of SA508 Gr.1a Low Alloy Steel in 310°C Deoxygenated Water

Abstract: The low cycle fatigue tests of SA508 Gr.1a low alloy steel in 310oC deoxygenated water were conducted to investigate the effect of cyclic strain rate on the environmentally assisted cracking (EAC) mechanisms. The flattened striations and the blunt crack tip, which indicate the occurrence of the slip dissolution/oxidation, were mainly observed for the specimen tested at 0.008 %/s. On the other hand, the brittle cracks and the blunt main crack with microcracks, which are the evidences of the hydrogen-induced cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The HIC is another important mechanism to decrease the fatigue life of austenite stainless steels in PWR water . The main source of hydrogen is the hydrogen gas purging process to reduce the DO content in the PWR water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HIC is another important mechanism to decrease the fatigue life of austenite stainless steels in PWR water . The main source of hydrogen is the hydrogen gas purging process to reduce the DO content in the PWR water.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental fatigue tests have mostly been carried out to evaluate the low cycle fatigue life of low alloy steels and austenitic stainless steel in the range of temperature, dissolved oxygen (DO), strain rate and the water flow rate of the PWR water condition . It has been reported that the fatigue life of austenitic stainless steel can be reduced in PWR water conditions where the DO content is extremely low . A probable mechanism is a hydrogen‐induced cracking (HIC) where the hydrogen ions are generated by an electrochemical reaction and diffused into the metal at the crack tip.…”
Section: Introductionmentioning
confidence: 99%